Pengaruh Ukuran Pemerintah Daerah, Kekayaan Daerah dan Belanja Daerah terhadap Internet Financial Reporting: Studi Empiris pada Kabupaten dan Kota di Pulau Sumatera - Amelia Omily; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2026)
This research aims to determine the influence of regional goverment size, regional wealth and regional spending on internet financial reporting. The population in this research are districts/cities on the island of Sumatera for the 2023 fiscal year using SPSS 24. This type of research uses a quantitative approach to test the relationship between the dependent variable and the independent variable . This research uses secondary data with a simple of 61 samples taken using the Slovin formula. Data analysis in this research uses multiple linear regression analysis to test the hypothesis. The results of this research show that regional wealth has a significant positive effect on internet financial reporting, while goverment size and regional spending do not have a significant effect on internet financial reporting.